Risk factors for contralateral hip refractures in patients aged over 80 years with intertrochanteric femoral fractures - Yu, Shujun; Li, Chen; Zhong, Yuqiao; Zang, Jiacheng; Zhou, Zhanzhe; Wang, Song; Zhang, Yinguang (Frontiers in Surgery, 2022)
Purpose: The purpose of this study was to identify which of the risk factors would contribute to the contralateral fracture in very elderly patients after intramedullary nails fixation. Methods: Clinical data of 227 intertrochanteric fracture patients who aged 80 years or older were retrospectively reviewed. Intramedullary nails (IMN) were used on all of the patients. Potential risk factors for contralateral hip refracture were determined using univariate and logistic regression analysis. Results: Contralateral hip refracture occurred in 11 patients (4.84%). Univariate analysis revealed that age, gender, BMI, fracture classification, hematocrit, D-dimer, and CRP level were not associated with contralateral fracture (P>0.05). However, neurological diseases, cardiovascular disease and visual impairments were significantly associated with contralateral fracture (P<0.05). Multivariate analysis further revealed that neurological diseases (OR 4.25, P=0.044) and visual impairments (OR 5.42, P=0.015) were independent risk factors associated with contralateral refracture. Conclusion: To prevent contralateral refracture, more attention should be paid to elderly intertrochanteric fracture patients with underlying neurological disease and visual impairments.